2018
DOI: 10.1016/j.chemphys.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Coherent dynamics in cavity femtochemistry: Application of the multi-configuration time-dependent Hartree method

Abstract: The photochemistry of a molecular ensemble coupled to a resonance cavity and triggered by a femtosecond laser pulse is investigated from a real-time, quantum dynamics perspective with the multi-configuration time-dependent Hartree method. Coherent excitation of a superposition of electronic states in the ensemble leads to superradiant energy transfer to the cavity characterized by quadratic scaling with the number of molecules. Electronic decoherence associated with loss of nuclear wave packet overlap among th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
132
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(133 citation statements)
references
References 59 publications
1
132
0
Order By: Relevance
“…Another promising trend in the field is development of (semi) ab-initio methods for nonadiabatic molecular polariton dynamics, as first proposed by Feist et al [175]. This integrative approach has been further developed by several groups [173,174,176,178,181,183,184,199,200]. The main strength of this methodology is its compatibility with conventional electronic structure and molecular dynamics techniques.…”
Section: B Recent Theoretical Progressmentioning
confidence: 99%
“…Another promising trend in the field is development of (semi) ab-initio methods for nonadiabatic molecular polariton dynamics, as first proposed by Feist et al [175]. This integrative approach has been further developed by several groups [173,174,176,178,181,183,184,199,200]. The main strength of this methodology is its compatibility with conventional electronic structure and molecular dynamics techniques.…”
Section: B Recent Theoretical Progressmentioning
confidence: 99%
“…In particular, real-time imaging of molecular dynamics can be achieved in experiments with a pump-probe setup with femtosecond resolution combined with the measurement of photoelectron spectra [31]. While similar approaches could in principle provide a dynamical picture of molecules under strong light-matter coupling [35][36][37], common molecular observables (such as dissociation or ionization yields or photoelectron spectra) are difficult to access in typical experimental setups, with molecules embedded in a solid-state matrix and confined within nanoscale cavities [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Polaritonic chemistry has become an emerging research field, aimed at providing new tools for the fundamental investigation of light-matter interaction. Since the pioneering experimental work carried out by the group of Ebbesen, in which they observed that strong light-matter coupling could modify chemical landscapes [8], the field of 'molecular polaritons' experienced much activity from both experimental [9][10][11][12][13][14][15][16][17][18][19] and theoretical [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] research groups. Recent achievements on molecules strongly coupled to a cavity mode, such as that strong cavity-matter coupling can alter chemical reactivity [9,38], provide long-range energy or charge transfer mechanisms [12,37], modify nonradiative relaxation pathways through collective effects [35], and modify the optical response of molecules [31,40], support the relevance of such a new chemistry.…”
Section: Introductionmentioning
confidence: 99%